Diarrhoeal pathogens in the stools of children living with HIV in Ibadan, Nigeria - Bejide, Oyeniyi S.; Odebode, Mariam A.; Ogunbosi, Babatunde O.; Adekanmbi, Olukemi; Akande, Kolawole O.; Ilori, Temitope; Ogunleye, Veronica O.; Nwachukwu, Victoria U.; Grey-Areben, Aghogho; Akande, Elizabeth T.; Okeke, Iruka N. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Diarrhoea can be debilitating in young children. Few aetiological investigations in Africans living with human immunodeficiency virus (HIV) have been performed since antiretrovirals became widely available. Methods Stool specimens from children with diarrhoea living with HIV, and HIV-uninfected controls, recruited at two hospitals in Ibadan, Nigeria, were screened for parasites and occult blood, and cultured for bacteria. Following biochemical identification of at least five colonies per specimen, diarrhoeagenic Escherichia coli and Salmonella were confirmed by PCR. Data were line-listed and comparisons were made using Fisher’s Exact test. Results Only 10 children living with HIV could be enrolled during the 25-month study period and 55 HIV-uninfected children with diarrhoea were included for comparison. The most common pathogens overall were enteroaggregative E. coli (18/65, 27.7%), enteroinvasive E. coli (10/65, 15.4%), Cryptosporidium parvum (8/65, 12.3%) and Cyclospora cayetanensis (7/65, 10.8%). At least one pathogen was detected from seven of ten children living with HIV and 27 (49.1%) HIV-uninfected children. Parasite detection was associated with HIV positive status (p=0.03) with C. parvum specifically recovered more commonly from children living with HIV (p=0.01). Bacterial-parasite pathogen combinations were detected in specimens from four of ten children living with HIV but only 3(5.5%) HIV-uninfected children (p=0.009). Stools from five of ten children living with HIV and 7(12.7%) HIV-negative children (p = 0.014) contained occult blood. Discussion Even though children living with HIV present infrequently to Ibadan health facilities with diarrhoea, their greater propensity for mixed and potentially invasive infections justifies prioritizing laboratory diagnosis of their stools.